A macro-modelling approach for arches strengthened with externally bonded inorganic matrix composites. (October 2021) - Pantò, Bartolomeo; Malena, Marialaura; de Felice, Gianmarco
Abstract: The use of externally bonded inorganic matrix composites is becoming a common technique for strengthening arches and vaults to improve the load-carrying capacity with respect to both static and seismic loads. Experimental evidence has shown a complex behaviour where failure may occur within the reinforcement matrix, with a strong coupling between pure opening mode (mode I) and shear mode (mode II), as a consequence of the curvature of the substrate. Aiming at providing a tool for simulating the structural behavior of masonry arches reinforced with inorganic matrix composites, a discrete macro-modeling approach is proposed in which the reinforcement is described by means of piecewise rigid plates, which interact with the masonry through zero-thickness nonlinear interfaces. A refined bond constitutive law, specifically conceived to account for both the cohesive and the frictional contributions, as well as the coupling between mode I and mode II, in terms of strength and softening behavior, is proposed and implemented in a macro-elements model. The proposed model is then validated through comparison with analytical predictions and experimental direct shear tests performed with straight and curved substrates. Eventually, the model is used to reproduce the behaviour of a barrel vault strengthened with steel reinforced grout and tested up to failure.